Morphology and molecular phylogenetic placement of a coastal shipworm (Bactronophorus thoracites (Gould, 1862), Teredinidae) from Peninsular Malaysia - Lee, Shiou Yih; Mohamed, Rozi; Lamasudin, Dhilia Udie (Elsevier, 2019)
The wood-boring shipworm, Bactronophorus thoracites (Teredinidae), is the only species in the genus Bactronophorus, with wide distribution in the Indo-West Pacific biogeographic region. Besides rendering important ecosystem services such as in decaying wood and participating in C fluxes in mangroves, to several ethnic groups in Southeast Asia, this mollusk is a highly nutritious delicacy when eaten raw. There are near 20 shipworm species reported in Malaysian waters, however, in-depth studies have not been conducted on any of these species. Here, we characterized B. thoracites from a mangrove environment on the west coast of Peninsular Malaysia. This bivalve is distinguished by its non-segmented pallet, composed of a basal cup with a dagger-like extension. Molecular phylogenetic analyses using 16S gene sequences from six different species (family Teredinidae) including B. thoracites, revealed a monophyletic relationship. On the contrary, combined datasets of 18S and 28S rRNA gene sequences from 12 different species (family Teredinidae) suggested a paraphyletic relationship; B. thoracites appeared to be a sister to Neoteredo reynei. Using the DNA barcode COI, B. thoracites is clearly separated from other teredinids, albeit with moderate bootstrap support. Molecular dating analysis speculated the divergence time between B. thoracites and N. reynei was the Early Cretaceous period. We provide novel DNA sequences for B. thoracites, which could be useful for species identity validation and molecular taxonomical studies.